1992
DOI: 10.1007/bf00317217
|View full text |Cite
|
Sign up to set email alerts
|

Response of invertebrates to lotic disturbance: a test of the hyporheic refuge hypothesis

Abstract: Recovery following hydrological disturbances is usually rapid for lotic invertebrates. Stream ecologists have assumed that recovery is facilitated by behavioral migrations during floods down into the hyporheic zone (the interstitial spaces of a streambed) to seek temporary refuge from possible erosion (the "hyporheic refuge hypothesis"). We provide the first explicit test of this hypothesis by evaluating three predictions of the hypothesis. We coupled field observations of the response of meiofaunal invertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
2
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 50 publications
7
156
2
2
Order By: Relevance
“…Evidence of benthos uti- Mixed (boulder, cobble, gravel and fi nes < 2 mm) eschweizerbart_xxx lisation of the hyporheic zone in perennial rivers and streams as a result of increased fl ows (spates/fl oods) is also equivocal (e.g., Palmer et al 1992, Dole-Olivier et al 1997, Fowler & Death 2001, Olsen & Townsend 2005, Olsen et al 2010. A number of studies have reported increased abundances of benthos within the hyporheic zone following spates, but also that the response was variable spatially (Dole-Olivier & Marmonier 1992, Dole-Olivier et al 1997.…”
Section: Utilization Of the Hyporheic Refuge Associated With River Flmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of benthos uti- Mixed (boulder, cobble, gravel and fi nes < 2 mm) eschweizerbart_xxx lisation of the hyporheic zone in perennial rivers and streams as a result of increased fl ows (spates/fl oods) is also equivocal (e.g., Palmer et al 1992, Dole-Olivier et al 1997, Fowler & Death 2001, Olsen & Townsend 2005, Olsen et al 2010. A number of studies have reported increased abundances of benthos within the hyporheic zone following spates, but also that the response was variable spatially (Dole-Olivier & Marmonier 1992, Dole-Olivier et al 1997.…”
Section: Utilization Of the Hyporheic Refuge Associated With River Flmentioning
confidence: 99%
“…This evidence appears to have been largely overlooked in the following years until freshwater scientists began to explore the vertical distribution of fauna within river beds (Coleman & Hynes 1970) leading to the 'hyporheic refuge hypothesis' proposed by Williams & Hynes (1974). Since then, the role of the hyporheic zone as a potential refugium has received increasing attention, with a particular emphasis on hydrological extremes associated with fl oods and droughts (Palmer et al 1992, Marchant 1995, Dole-Olivier et al 1997, Stubbington et al 2009a, Robertson & Wood 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque los organismos acuáticos exhiben algún grado de resiliencia al disturbio (Palmer et al, 1992) también son susceptibles a alteraciones del hábitat (Gorman y Karr, 1978;Pretty et al, 2003). Alteraciones como la canalización, desvío y represamiento de los cauces pueden afectar de diversas formas el hábitat de la biota acuática (Fig.…”
Section: ¿Cuáles Son Los Potenciales Efectos De Las Modificaciones Deunclassified
“…Toutefois, Giberson & Hall (1988) n'observent pas de variations saisonnières des invertébrés autres que les insectes dans un cours d'eau canadien ; Kowarc (1991) La persistance observée sur le Nert implique donc que la communauté des Crustacés de ce site n'est pas influencée par les perturbations de l'environnement. Parmi ces dernières, les crues sont considé-rées comme un des facteurs essentiels de déstabili-sation du milieu hyporhéique (Williams & Hynes 1974, Danielopol 1976, Marmonier & Dolé 1986, Marmonier 1988, Strommer & Smock 1989 Dole et Marmonier 1992, Palmer 1990, Palmer et al 1992. Sur le Nert, lors de l'année étudiée, comme sur le Lachein (Rouch 1988), les crues n'ont modifié ni la morphologie du lit, ni la structure globale des écou-lements interstitiels (Rouch 1992, Rouch et al sous presse) ni la structure des peuplements.…”
Section: Persistanceunclassified